2014
DOI: 10.1021/bm5012739
|View full text |Cite
|
Sign up to set email alerts
|

Fully Biobased and Supertough Polylactide-Based Thermoplastic Vulcanizates Fabricated by Peroxide-Induced Dynamic Vulcanization and Interfacial Compatibilization

Abstract: A fully biobased and supertough thermoplastic vulcanizate (TPV) consisting of polylactide (PLA) and a biobased vulcanized unsaturated aliphatic polyester elastomer (UPE) was fabricated via peroxide-induced dynamic vulcanization. Interfacial compatibilization between PLA and UPE took place during dynamic vulcanization, which was confirmed by gel measurement and NMR analysis. After vulcanization, the TPV exhibited a quasi cocontinuous morphology with vulcanized UPE compactly dispersed in PLA matrix, which was di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(161 citation statements)
references
References 54 publications
6
153
2
Order By: Relevance
“…7 shows the SEM micrographs of cryo-fractured surfaces of both regular and annealed injection molded samples. Although phase-separated morphology is observed for all the samples, no obvious gaps between dispersed VUB and polylactide matrix could be observed, indicating strong interfacial adhesion between VUB and the matrix due to the interfacial compatibilization [30]. It is hard to discriminate VUB phase from the matrix for regular injection molded PLLA/VUB binary ( Fig.…”
Section: Degree Of Crystallinitymentioning
confidence: 92%
See 3 more Smart Citations
“…7 shows the SEM micrographs of cryo-fractured surfaces of both regular and annealed injection molded samples. Although phase-separated morphology is observed for all the samples, no obvious gaps between dispersed VUB and polylactide matrix could be observed, indicating strong interfacial adhesion between VUB and the matrix due to the interfacial compatibilization [30]. It is hard to discriminate VUB phase from the matrix for regular injection molded PLLA/VUB binary ( Fig.…”
Section: Degree Of Crystallinitymentioning
confidence: 92%
“…Succinic acid (SA), adipic acid (AA), 1,4-butanediol (BDO), tetraisopropyl titanate (TIPT), hydroquinone monomethyl ether (MEHQ) and dicumyl peroxide (DCP) were all obtained from Kelong Chemical Factory (Chengdu, China). UBE with M w and PDI of 1.79×10 5 g mol −1 and 3.24 was prepared from condensation polymerization of SA, AA, IA, and BDO with mole ratio of 0.35/0.55/0.10/1.05 with 0.05 wt.% MEHQ and 0.1 wt.% TIPT as the inhibitor and catalyst, respectively, according to the procedure reported previously [30]. All chemicals were used without purification, and PLLA, PDLA and UBE were vacuum dried at 80°ʠ prior to further processing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a ternary blend consisting of PLA, PC, and poly(butylene adipate-coterephthalate) (PBAT) was fabricated to obtain a novel material with unique properties including high toughness and good biodegradability [37]. Recently, a bio-based vulcanized unsaturated aliphatic polyester elastomer (UPE) was used to fabricate a super-tough thermoplastic blends containing PLA [30,38]. The results showed that the interfacial compatibilizations between PLA and UPE would lead to improved tensile and impact toughness with values up to ~99 MJ/m 3 and ~586 J/m, respectively, as compared to those of ~3.2 MJ/m 3 and ~16.8 J/m for neat PLA, respectively.…”
Section: Mechanical Propertiesmentioning
confidence: 99%